Energy decompositions according to physical space partitioning schemes: Treatments of the density cumulant - Alcoba, D.R. (2007)
This article is a continuation of our previous paper on schemes of energy decompositions of molecular systems in the real space [D. R. Alcoba, J. Chem. Phys. 122, 074102 (2005)] now using correlated state functions. We study, according to physical arguments, the appropriate management of the density cumulant arising from the second-order reduced density matrix at correlated level, whose contributions can be assigned to one-center or to two-center terms in the energy partitioning. Our treatments are applied within two physical space partitioning schemes: the Bader partitioning into atomic basins and the fuzzy atom procedure. The results obtained in selected molecules are analyzed and discussed in detail. © 2007 American Institute of Physics.